QUANTITATIVE STUDY OF THE WORLD MARKET OF MEAT - Elena COFAS; Elena SOARE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2013)
This study presents the evolution of global market of meat in 2007-2011 and has been possible because the authors used an important set of indicators, namely: livestock, achieved production, imports, exports, trade balance, price etc. The data used in this work was provided by the following institutions accredited for collecting and processing statistical data: National Institute of Statistics, EUROSTAT, FAOSTAT, FAPRI and USDA. The analysis global market of meat is primarily a quantitative analysis. In the period which is analysed, the demand, the production, the imports, the exports and the prices have evolved differently, especially meat categories, so all these indicators have influenced global market of meat. In mainly, the meat consumption is influenced by the pattern of food consumption and price level. In the future, expect a increase prices, which is based on increasing production costs. Therefore, first it is necessary to adopt measures to support the farmers.